Acute Pancreatitis Secondary to a Perivaterian Duodenal Diverticular Abscess. (29th November 2010) - Pastides, P.; Bertaud, S.; Sarker, S. K.; Dindyal, S.
Abstract : A 46-year-old previously fit lady was admitted with acute pancreatitis. She had no history of gallstones. She was not on any medications and consumed minimal amounts of alcohol. On subsequent investigations as to the causative factor, she was found at ultrasound to have an air-fluid filled cystic structure posterior to the head of pancreas which was compressing the common bile duct. Further magnetic resonance imaging and computer tomography scans showed that this cystic lesion was located around the ampulla of Vater. A diagnosis of a perivaterian abscess was made. At endoscopy, a large contained abscess was seen which was successfully drained. She made a full and uneventful recovery.